Diversifikasi produk olahan ikan lele (Clarias sp.) berbasis zero waste di UMKM Suole (Sukorejo olahan lele) - Andriani, Nani; Sholiha, Illiyatus; Ikerismawati, Senja (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2025)
African catfish (Clarias sp.) is an aquaculture commodity with considerable potential to support food security and community economic development. However, its utilization is still predominantly limited to fresh fish products with relatively low added value. This study aimed to describe the diversification of processed African catfish products based on the zero waste concept at UMKM SUOLE (Sukorejo Olahan Lele) and to identify the potential for increasing added value through the utilization of all parts of the fish. The research employed a qualitative descriptive method with a case study approach, using observation, interviews, and direct involvement in the production process. The results showed that UMKM SUOLE has developed various processed African catfish products, including shredded catfish, catfish bone sticks, catfish skin crackers, catfish nuggets, and catfish dim sum. This product diversification enables the optimal utilization of catfish meat, bones, and skin, thereby supporting the implementation of the zero waste concept. Processing African catfish into value-added products not only extends shelf life and increases product market value but also has the potential to enhance UMKM income and reduce fisheries processing waste. Therefore, zero waste-based diversification of processed African catfish products can serve as a sustainable and competitive development strategy for fisheries-based UMKMs.